Ficino, Pico and Savonarola : the evolution of humanist theology 1461/2-1498 - Edelheit, Amos, Ph.D. (Leiden ; Boston : Brill, 2008)
Presents a study of humanism, theology, and politics in Florence during the last decades of the fifteenth century. This book offers an account of Ficino's De Christiana religione and of Pico's Apologia, in the context of the evolution of a humanist theology. It also focuses on the relations between humanism, theology, and politics.
Giovanni Caroli, the conduit of the sense of spiritual and political crisis in Florence -- Introduction: Giovanni Caroli and his times -- Liber dierum lucensium : Prooemium and book one -- Liber dierum lucensium, book two -- Liber dierum lucensium, book three -- Humanist theology in practice -- The historical context -- Declamationum liber -- The Turkish danger and its religious connotations -- Classical, biblical, and patristic allusions : the disappearance of the doctors -- The attitude to rhetoric -- Ficino's praedicationes -- Poliziano's sermons -- Rinuccini's sermons -- Nesi's sermons -- Other sermons -- Marsilio Ficino and the conditio religionis : quandiu duram et miserabilem hanc ferrei seculi sortem sustinebimus? -- Some general introductory remarks -- De christiana religione : the "manifesto" of the new humanist theology -- Prisca religio and its divine inspiration : religion as the characteristic of man -- Praeparatio evangelica -- The incarnation as an intervention of the eternal in the temporal -- The teachings of Christ -- The apostles and the propagation of Christianity -- The decline of the Christian world and Ficino's proposals for renewal -- Giovanni Pico della mirandola and his theological method : between Opinio and fides -- The theological crisis -- Quia errare in opinione thomae, non est errare in fide-the dispute in Rome 1486 and the Apiologia -- Pico's attitude to philosophy : between academic skepticism and religious certainty -- The Savonarola affair-the government of God as republican practice -- The Savonarola a'air : a case-study in the history and in the historiography of the Renaissance -- Savonarola : an anti-humanist or a pro-humanist? -- Savonarola and politics -- The notion of reform : the transition from theology to politics -- Spiritual and political vision : the preaching prophet and his slogan.
Includes bibliographical references (pages 469-483) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 600
Keywords: Ficino, Marsilio, -- 1433-1499.; Pico della Mirandola, Giovanni, -- 1463-1494.; Savonarola, Girolamo, -- 1452-1498.; Ficino, Marsilio; Pico della Mirandola, Giovanni; Savonarola, Girolamo; Christianity and religious humanism; Humanism -- Italy -- Florence -- History; Philosophical anthropology; Theological anthropology; RELIGION -- Christianity -- History; Christentum; Humanismus; Florenz; Italien; Geschichte 1461-1498; Electronic books